Amapola Club Reunion at 1959 Homecoming photo and identification guide (1959)
Group portrait of the Amapola Club reunion at the 1959 Homecoming. The group attended Cal Poly in the 1920s. Includes a guide on the back of the photograph to naming the people in the Amapola Club group photograph. Includes key, list of names, and short description. 'The Amapola Club, composed of women on the campus of California State Polytechnic College, San Luis Obispo, in the 20's, held a reunion at the school during the 1959 Homecoming. They plan to make their get-together an annual event. In the following identifying caption, maiden names are shown in parentheses. 1 -- Fay Wallin (Rougeot), 101 Auto Court, Arroyo Grande 2 -- Mrs. Cecile Austin (Bello), 1890 Fixilini St., San Luis Obispo 3 -- Charlotte J. Smith, Santa Margarita 4 -- Mrs. J.T. Hewson (Aileen Booker), 901 Osos St, San Luis Obispo 5 -- Tekla Johnson, Route 1, Box 63 Templeton 6 -- Hazel Stewart (True), 2128 Cove St., Los Angeles 7 -- Mrs. Stella Louis, 350 Lincoln Ave., San Luis Obispo 8 -- Mrs. Gertrude Haley (Truesdale), 1251 Sage St., Arroyo Grande 9 -- Mrs. Don Johnson (Mayhall), Oceano 10 -- Mrs. Margaret Coyner (Ditmas?), 1832 Corralitos Dr., San Luis Obispo 11 -- Mrs. Jewett Johnson, 875 Mountain View, San Luis Obispo 12 -- Mrs. Howard O'Daniels (Mary Hughes), 1755 Corralitos Dr., San Luis Obispo 13 -- Mrs. Helene Hailey (Van Gorden), 727 East Church, Santa Maria 14 -- Mrs. Pearl Buck (Bardmess), 1349 Chorro St., San Luis Obispo 15 -- Mrs. Hulda Washburn (Bordine), 1760 Johnson Ave., San Luis Obispo 16 -- Mrs. Harriett Zanoli (Wright), 888 Vanable St., San Luis Obispo 17 -- Mrs. Alta Fae Baker (Mayhall), 1300 E. Park, Grants Pass, Oregon 18 -- Mrs. Maxine Van Schaick (Barneberg), 531 Dana St., San Luis Obispo 19 -- Mrs. Ethel Holt (Van Schaick), 904 Meinecke St., San Luis Obispo 20 -- Mrs. Leona Stenner (Forbes), 65 Cass St., San Luis Obispo 21 -- Elsbeth Giorgi (Meinecke), Atascadero 22 -- Mrs. Margaret Weant (Meinecke), 75 Santa Rosa St., San Luis Obispo 23 -- Mrs. Elgin Knott (Pearl Knott), 1418 Johnson Ave., San Luis Obispo 24 -- Mrs. Margaret Nelson (Truesdale), 644 Mountain View, San Luis Obispo 25 -- Mrs. Z. Terri, Guest 26 -- Mrs. Ethel Pearce, Guest 27 -- Mrs. Delis Reinert (Irving), Templeton 28 -- Marie Taylor (Meinecke), 618 Mira Monte St., Santa Barbara 29 -- Diana Reinert, Guest 30 -- Miss Margaret Chase, 1355 Mill St., SLO 31 -- Mrs. Shirley McMillan (Dunning), Shandon 32 -- Blanche Birra (Guimini), 2605 Flera St., San Luis Obispo 33 -- Betty Stewart, Guest, 2128 Cove St., Los Angeles